A Pilot Evaluation of Portfolios for Quality Attestation of Clinical Ethics Consultants. Issue 3 (3rd March 2016) - Fins, Joseph J.; Kodish, Eric; Cohn, Felicia; Danis, Marion; Derse, Arthur R.; Dubler, Nancy Neveloff; Goulden, Barbara; Kuczewski, Mark; Mercer, Mary Beth; Pearlman, Robert A.; Smith, Martin L.; Tarzian, Anita; et al.
Abstract : Although clinical ethics consultation is a high-stakes endeavor with an increasing prominence in health care systems, progress in developing standards for quality is challenging. In this article, we describe the results of a pilot project utilizing portfolios as an evaluation tool. We found that this approach is feasible and resulted in a reasonably wide distribution of scores among the 23 submitted portfolios that we evaluated. We discuss limitations and implications of these results, and suggest that this is a significant step on the pathway to an eventual certification process for clinical ethics consultants.